Now or later? Fertility intentions in Bulgaria and Hungary and the impact of anomie and social capital - Dimiter Philipov; Zsolt Spéder; Francesco C. Billari (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2005)
This paper discusses the construction of fertility intentions in contemporary Bulgaria and Hungary. It presents empirical analyses of four types of fertility intentions: whether to have or not to have a first or a second child and if yes, whether to have this child within the next two years or later. Both countries have recently experienced drastic societal transformations. Based on comparative survey data for women we find that that explanatory factors of fertility intentions differ significantly by order of an intended birth and its timing. We attribute particular emphasis to social anomie and social capital as important factors in shaping fertility intentions and in timing a desired birth. Moreover, economic factors are important determinants in Bulgaria, while ideational and demographic factors are significant in both countries. The findings suggest the necessity of explicitly taking into account birth order and the timing of a desired birth in large-scale demographic surveys and the importance of anomie and social capital in recent fertility choices in Central and Eastern Europe.
Keywords: 300; Fertility intentions; fertility in Bulgaria; fertility in Hungary; social capital; social anomie; Fertilität; Familienplanung; Humankapital; Bulgarien; Ungarn